Employees at work in Dearborn Chemical Company offices - Dearborn Chemical Company (1927)
General view of male and female employees at work at the Dearborn Chemical Company's 35th Street laboratory facility and manufacturing plant. Founded in 1887, the Dearborn Chemical Company was a corporate ancestor of BetzDearborn, Incorporated best known for manufacturing water treatment chemicals for use in boilers and cooling towers.
Keywords: Employees; Chemical industry; Dearborn Chemical Company; Corporations; Women employees